NUTRITIONAL AND ROTI QUALITY OF SORGHUM GENOTYPES - Chavan, U.D.; Patil, J.V.; Shinde, M.S. (Indonesian Agency for Agricultural Research and Development - MOA, 2009)
Sorghum grains are mostly used for the roti preparation. TheM 35-1 (Maldhandi) a sorghum cultivar is known for its goodquality of roti due to having pearly white grain color, its flourhaving higher water holding capacity, and good organoleptictaste. However, this cultivar is low yielder. To evolve sorghumhigh yielding genotype coupled with this good roti qualities,systematic breeding program was planned and executed toovercome this problem. Twenty local land races, 92 genotypes,and seven improved cultivars of sorghum along with check M35-1 were studied for various nutritional quality parameters,with special reference to the roti quality. Considering nutritionalquality and organoleptic evaluation parameters studied for rotiquality, the local land races viz., RSLG 428-1, RSLG 1238,RSLG 1275 and the genotypes viz., RSV 290, RSV 292, RSV858, RSV 859, RSV 861, RSV 868, RSV 894, RSV 985, RSV 992,RSV 995, RSV 999 were found to be promising for protein,sugar, water absorption, and soluble protein content. Therefore,they can be used for further improvement in nutritional qualitythrough breeding program. Among the improved cultivars, PhuleVasudha (RSV 423), CSV 22, and Phule Chitra (SPV 1546) werefound to be most promising for roti quality. The maximum scorefor overall acceptability was found for Phule Vasudha followedby Phule Anuradha (RSV 458), Phule Yeshoda (RSLG 262), andPhule Maulee (CSV 216).